The Effect of Agility Ladder Drill Training on The Footwork Agility of Karate Athletes in The Kumite Class at Bushido - Muhamad Almaas Atha Hilal; Roas Irsyada (Universitas Negeri Semarang, 2026)
This study aims to determine the effect of the Agility Ladder Drill on the foot agil-ity of karate athletes in the kumite class at the Bushido One Club in Tegal Regen-cy. The study was conducted using a one-group pretest-posttest design and em-ployed the Illinois Agility Test to measure the agility of the participants. This study involved a sample of 20 karate athletes competing in the kumite class. The results of the Paired Samples T-test showed that the mean difference between the pre-test and post-test was 0.77750 with a standard deviation of 0.48070 and a significance level of <0.001 (<0.05). Consequently, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) accepted, indicating a significant difference following the intervention. It can therefore be concluded that the Agility Ladder Drill programme, comprising 14 sessions with a training schedule of three sessions per week, is effective in improving the foot agility of Bushido One Club karate athletes competing in the kumite category.